Applied Accounting Concepts and Standards in Indonesian Business Realities - Victor Pattiasina; La Ode Marihi; Mohammad Amin Watimena; Andarias Patiran; Rahma Satya Masna Hatuwe; Leonora Ferdinandus; Marie C. Tahalele (Journal of Business Application, 2025)
Indonesia has adopted IFRS as an accounting standard in making a quality report. IFRS standards that have been set are certainly not free of obstacles, this then becomes a challenge in implementing accounting standards in accordance with IFRS standards. So, to prepare an accounting financial report, practical aspects of accounting in Indonesia with applicable standards are needed in relation to the implementation of the principles of accounting standards in everyday life involving companies, accountants, and practitioners. The method used in this research uses a qualitative descriptive approach using a literature study with data sources derived from secondary data in the form of books, scientific journals, articles and research reports. The results obtained from the discussion are the practical aspects of accounting in Indonesia in the application of accounting concepts and standards in real situations involving companies, accountants, and accounting practitioners that must be considered, namely practical aspects in the application of accounting standards, measurement of assets and liabilities, revenue recognition, tax measurement, complete disclosure, internal audits and examinations, professional ethics, and management decision making.